MIASMATIC INFLUENCE ON MORAL CONSCIOUSNESS-A CASE REPORT EXPLORING THE IMPACT OF ANTIMIASMATIC MEDICINE ON MORALITY - Kulkarni Vibhuti Ashok; Dr. K. B. Shah (The Bioscan, 2025)
A study had been conducted for the comprehension of the influence of miasm on the moral values of various types of individuals. The focus of the study was to understand the effect of inherent miasm on the developmental psychology of the student age group. For serving this purpose a case report has shown in this article; a case was treated with the intervention of individualistic homoeopathic medicine. KEYWORDS Miasm, morality, case study showing effectiveness of treatment.